Analisis Pengembangan Sumber Daya Manusia dan Budaya Sekolah Dalam Peningkatan Kinerja Guru Dampaknya terhadap Disiplin Kerja Guru (Studi pada Guru SMA Negeri se-Kabupaten Pidie) - Faisal, Faisal; Ibrahim, Ibrahim; Tawakal, Tawakal (peusangan, 2024)
Teacher resources are important in producing excellent schools, when their performance meets standards. Teacher performance studies are inseparable from factors that are directly and indirectly involved. Therefore, this case study research in Pidie Regency High School analyzes human resource development factors, school culture on teacher performance that have an impact on teacher discipline. Using associative quantitative methods with path analysis based on a sample of 288 teachers. The results obtained were that: 1) there is a direct and indirect influence of human resource development on teacher performance of 31.6 percent, and a direct and indirect influence of school culture on teacher performance of 48.21 percent. 2) Simultaneously, human resource development and school culture make a positive contribution of 74,7 percent. 3) there is a direct and indirect influence of human resource development on teacher work discipline of 22.22 percent, and a direct and indirect influence of school culture on teacher work discipline of 27.96 percent. 4) There is an influence of human resource development and school culture on work discipline through teacher performance of 17.99 percent.